Beer Tourism in South Africa - Christian M. Rogerson; Keagan J. E. Collins (Nordic Journal of African Studies, 2015)
Beer tourism is a growing dimension of culinary or food tourism. In terms of culinary tourism South Africa is traditionally associated with wine tourism. However, the country is experiencing the rise of beer tourism. Against the background of international research on beer tourism the paper examines the emergence, growth and changing directions of South African beer tourism. It is argued that the current focus in beer tourism is upon the country’s expanding network of craft beer micro-breweries and associated organized beer festivals. Beer tourism offers opportunities for driving tourism development in several destinations including small town South Africa.